Effect of Biomass Waste and CaO Blend Compositions on the Pelletizing Characteristics of Refuse-Derived Fuel (RDF) - Lusi Ernawati; Rizqy Romadhona Ginting; Rizka Lestari; Apip Amrullah; Obie Farobie; Pandji Prawisudha; Muhammad Raihan; Pangga Apriliawan (International Journal of Marine Engineering Innovation and Research, 2025)
Refuse-Derived Fuel (RDF) is increasingly acknowledged as a sustainable method of managing municipal solid waste while simultaneously producing valuable energy. However, the quality and compactness of RDF as a fuel can vary substantially depending on the materials used to produce it. The incorporation of biomass waste and calcium oxide (CaO) significantly influences the pelletizing behavior of biopellets by altering their physical and thermal properties, which in turn determines their effectiveness and suitability as a fuel source. In this study, representative RDF pellets were prepared by blending four primary components: wood sawdust, organic waste, plastic waste, and a fixed proportion of CaO. The investigation focused on assessing the effects of varying biomass waste-to-organic waste ratios on the physicochemical characteristics, densification behavior, and proximate properties of typical RDF pellets. The experimental design included biomass-to-organic waste ratios of 1:1, 2:1, 3:1, 4:1, 5:1, and 6:1 while the proportions of plastic (20 wt%) and CaO (5 wt%) were held constant. The findings revealed that optimal RDF performance was achieved at biomass-to-organic waste ratios of 1:1 and 6:1, respectively. The resulting RDF pellets exhibited the following properties: ash content of 7.04 ± 8.78%, moisture content of 8.19 ± 8.82%, volatile matter ranging from 65.11 ± 66.19%, fixed carbon content of 13.95 ± 17.32%, calorific values between 4193 ± 4419 kcal·kg-1, and bulk densities of 0.98 ± 1.18 kg·dm-3. These results highlight the potential of RDF pellets as a promising alternative fuel source for boiler applications.